Phosphorylation of Smad2/3 at the specific linker threonine residue indicates slow‐cycling esophageal stem‐like cells before re‐entry to the cell cycle. Issue 2 (29th August 2014) - Takahashi, Y.; Fukui, T.; Kishimoto, M.; Suzuki, R.; Mitsuyama, T.; Sumimoto, K.; Okazaki, T.; Sakao, M.; Sakaguchi, Y.; Yoshida, K.; Uchida, K.; Nishio, A.; et al.
Summary: The stem cell compartment in the esophageal epithelium is possibly located in the basal layer. We have identified significant expression of Smad2/3, phosphorylated at specific linker threonine residues (pSmad2/3L‐Thr), in the epithelial cells of murine stomach and intestine, and have suggested that these cells are epithelial stem cells. In this study, we explore whether pSmad2/3L‐Thr could serve as a biomarker for esophageal stem cells. We examined esophageal tissues from normal C57BL/6 mice and those with esophagitis. Double immunofluorescent staining of pSmad2/3L‐Thr with Ki67, CDK4, p63, or CK14 was performed. After immunofluorescent staining, we stained the same sections with hematoxylin‐eosin and observed these cells under a light microscope. We used the 5‐bromo‐2‐deoxyuridine (BrdU) labeling assay to examine label retention of pSmad2/3L‐Thr immunostaining‐positive cells. We collected specimens 5, 10, 15 and 20 days after repeated BrdU administrations and observed double immunofluorescent staining of pSmad2/3L‐Thr with BrdU. In the esophagus, pSmad2/3L‐Thr immunostaining‐positive cells were detected in the basal layer. These cells were detected between Ki67 immunostaining‐positive cells, but they were not co‐localized with Ki67. pSmad2/3L‐Thr immunostaining‐positive cells showed co‐localization with CDK4, p63, and CK14. Under a light microscope, pSmad2/3L‐Thr immunostaining‐positive cells indicated undifferentiated morphological features. Until 20 days follow‐up period, pSmad2/3L‐Thr immunostaining‐positive cells were co‐localized with BrdU. pSmad2/3L‐Thr immunostaining‐positive cells significantly increased in the regeneration phase of esophagitis mucosae, as compared with control mice (esophagitis vs. control: 6.889 ± 0.676/cm vs. 4.293 ± 0.659/cm; P  < 0.001). We have identified significant expression of pSmad2/3L‐Thr in the specific epithelial cells of murine esophagi. We suggest that these cells are slow‐cycling epithelial stem‐like cells before re‐entry to the cell cycle.